The Potential for On-Site Determination of Mn(II) using Eco-Friendly Natural Tannins: A Cost-Effective and Sustainable Approach - Ola, Pius Dore; Kothan, Domonika Pransa; Suwari, Suwari; Kadang, Luther; Darmakusuma, Dodi (Indonesian Journal of Chemical Research, 2025)
This study exploited digital image colourimetry (DIC) with natural tannin as a reagent to determine Mn(II) in aqueous media. The calibration curve had a correlation coefficient of 0.995, indicating a strong dependence of absorbance on Mn(II) concentration. Although the spectrophotometry method with NaIO4 as a reagent showed better results, the DIC method remained within an acceptable range. Both methods showed insignificant difference in measurement average and variance. Common cations in natural water interfered with Mn(II) detection at a tolerance of less than 5% except for Fe(III), which can be easily precipitated before Mn(II) analysis. The DIC method applied to three water samples showed acceptable recovery, offering an easy and inexpensive on site Mn(II) determination.